PENGARUH EARNING PER SHARE, RETURN ON ASET DAN DEBT TO EQUITY RATIO TERHADAP RETURN SAHAM PADA PT BANK SINARMAS TBK PERIODE 2014-2023 - Ayu Lowrensia Napitupulu; Dede Hendra (Journal of Research and Publication Innovation, 2024)
This study aims to determine the impact of Earnings Per Share (EPS), Return On Assets (ROA), and Debt to Equity Ratio (DER) on stock returns at Bank Sinarmas Tbk for the period 2014-2023, both partially and simultaneously. The research employs a descriptive quantitative approach with primary and secondary data sources. Sampling is conducted using purposive sampling, resulting in a 10-year sample. Data analysis techniques include Multiple Regression Testing, Descriptive Statistical Testing, and Classical Assumption Testing, which covers Normality Test, Multicollinearity Test, Heteroscedasticity Test, and Run Test. Data analysis is performed using SPSS version 29. The partial t-test results reveal that EPS, ROA, and DER do not significantly affect stock returns, with significance values of 0.954, 1.795, and 1.479, respectively, all exceeding the 0.05 threshold. Simultaneously, EPS, ROA, and DER collectively do not significantly impact stock returns. The Determination Test results indicate an Adjusted R Square value of 0.392, suggesting that EPS, ROA, and DER explain 39.2% of the variation in stock returns, while the remaining 60.8% is influenced by other factors not examined in this study.